CRIMINATION OF CRIMINAL ACTS OF KHAMAR AND DRUGS IN ISLAMIC CRIMINAL LAW COMPARED TO INDONESIAN POSITIVE CRIMINAL LAW - Hulaimi Hulaimi; Lewiaro Laia; Khairul Azwar Anas (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
Narcotics and dangerous drugs may be as old as humans. Increasingly, drug users are increasingly widespread in various parts of the world, including Indonesia. The types of drugs are getting more and more sophisticated. In this latest century, it seems that no country is free from the problem of drugs. The term drugs in the context of Islamic law, is not mentioned directly in the Qur'an or in the Sunnah. In the Koran only mentions the term khamr. The purpose of this study is to analyze the comparison of punishment for perpetrators of the crime of alcohol and drugs in Islamic criminal law compared to positive Indonesian criminal law with normative legal research methods. The criminal difference for the perpetrators of the crime of khamr in Islamic criminal law compared to positive Indonesian criminal law is that in Islamic law, the punishment imposed is only in the form of caning, while in positive Indonesian criminal law, the sentence imposed can be in the form of imprisonment or a related fine. with liquor which is classified as a